PENGARUH MEDIA BLOK PECAHAN TERHADAP KEMAMPUAN PEMAHAMAN KONSEP SISWA PADA PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Hasnaa Masyitah; Nida Jarmita; Azmil Hasan Lubis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Learning fractions is often challenging for elementary school students because the concepts are abstract and require concrete representation to be understood effectively. This study aims to examine the effect of fraction block media on students’ conceptual understanding in elementary mathematics learning. This research employs a quantitative method with an experimental approach. The research design used is a pre-experimental One Group Pretest–Posttest design. The population in this study consisted of third-grade elementary school students, who were also selected as the sample through total sampling. Research data were collected using a test technique and analyzed using a t-test. The results of the study indicate that fraction block media has a significant effect on students’ conceptual understanding in mathematics learning. This is evidenced by the independent t-test showing a significance value of <0.05, which means there is a difference in students’ conceptual understanding before and after learning mathematics using fraction block media. These findings confirm the purity of the media’s influence on students’ conceptual understanding without dominant interference from external variables. Therefore, it can be concluded that fraction block media is effective in improving students’ conceptual understanding of fractions. The implications of this study suggest that teachers are encouraged to use concrete instructional media in mathematics learning to optimize student understanding.